Global state of education-related inequality in COVID-19 vaccine coverage, structural barriers, vaccine hesitancy, and vaccine refusal: findings from the Global COVID-19 Trends and Impact Survey. Issue 2 (February 2023) - Bergen, Nicole; Kirkby, Katherine; Fuertes, Cecilia Vidal; Schlotheuber, Anne; Menning, Lisa; Mac Feely, Stephen; O'Brien, Katherine; Hosseinpoor, Ahmad Reza
Summary: Background: COVID-19 vaccine coverage and experiences of structural and attitudinal barriers to vaccination vary across populations. Education-related inequality in COVID-19 vaccine coverage and barriers within and between countries can provide insight into the hypothesised role of education as a correlate of vaccine access and acceptability. We aimed to characterise patterns of within-country education-related inequality in COVID-19 vaccine indicators across 90 countries. Methods: This study used data from the University of Maryland Social Data Science Center Global COVID-19 Trends and Impact Survey. Data from 90 countries (more than 14 million participants aged 18 years and older) were included in our analyses. We assessed education-related inequalities globally, across country-income groupings, and nationally for four indicators (self-reported receipt of COVID-19 vaccine, structural barriers to vaccination, vaccine hesitancy, and vaccine refusal) for the study period June 1–Dec 31, 2021. We calculated an absolute summary measure of inequality to assess the latest situation of inequality and time trends and explored the association between government vaccine availability policies and education-related inequality. Findings: Nearly all countries had higher self-reported receipt of a COVID-19 vaccine among the most educated respondents than the least educated respondents. Education-related inequality in structural barriers, vaccine hesitancy, and vaccine refusal varied across countries, and was most pronounced in high-income countries, overall. Low-income and lower-middle-income countries reported widespread experiences of structural barriers and high levels of vaccine hesitancy alongside low levels of education-related inequality. Globally, vaccine hesitancy in unvaccinated people was higher among those with lower education and vaccine refusal was higher among those with higher education, especially in high-income countries. Over the study period, education-related inequalities in self-reported receipt of a COVID-19 vaccine declined, globally and across all country income groupings. Government policies expanding vaccine availability were associated with lower education-related inequality in self-reported receipt of vaccine. Interpretation: This study serves as a baseline for continued inequality monitoring and could help to inform targeted actions for the equitable uptake of vaccines. Funding: Gavi, the Vaccine Alliance.